Evaluation of lipid profile pattern and atherogenic index of plasma (AIP) having type-2 diabetes mellitus in Bangladesh - Anjum, Mahfuza; Uddin, Md. Salah; Tamanna, Naima Ahmed; Al-Zobair, Md. Abdullah; Mijanur Rahman, A. T. M. (International Journal of Research in Medical Sciences, 2018)
Background: Dyslipidemia has been noted to play an integral role in the pathogenesis and progression of micro and macrovascular complications in Diabetes Mellitus (DM) patients. The study was aimed to evaluate the prevalence and pattern of dyslipidemia and atherogenic index of plasma (AIP) in type 2 diabetes mellitus patients as it has not been reported previously in Bangladesh Methods: This cross-sectional study was conducted at Armed Forces Institute of pathology, Bangladesh from November 2016 to October 2017. A total number of 300 patients having diabetes in the age group of 30-60 years have been selected using a non-probability method. Fasting plasma glucose (FPG), serum total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C) and triglyceride (TG) levels were estimated by laboratory tests. Results: The prevalence of dyslipidemia in at least one lipid parameter was found in 282 patients (94%), while 18 patients (6%) had no dyslipidemia. High levels of TC, TG and LDL-C were found in 134 (47.3%), 230 (76.7%) and 124 (41.3%) patients, respectively. On the other hand, low levels of HDL-C were found in 180 patients (60%). An increased risk of AIP was found in 298 patients (99.3%), whereas only 2 patients (0.7%) were in low risk. FPG was positively correlated with TC, TG, LDL-C and AIP, while negatively correlated with HDL-C. A significant positive correlation was also observed between FPG and AIP. Conclusions: The Study revealed that dyslipidemia is very common in type 2 diabetic patients and the most common abnormality observed was increased serum triglyceride levels followed by decreased serum HDL-C levels. The AIP is also significantly higher in type 2 diabetic patients.